Identification and validation of potential prognostic biomarkers in glioblastoma via the mesenchymal stem cell infiltration level - Wang, Shengyu; Mao, Senlin; Li, Xiaofu; Yang, Dan; Zhou, Yinglian; Yue, Hui; Li, Bing; Li, Wei; Li, Chengyun; Zhang, Xuemei (Frontiers in Oncology, 2024)
Mesenchymal stem cells (MSCs) are key components in promoting glioblastoma (GBM) progression.This study aimed to explore new therapeutic targets and related pathogenic mechanisms based on different MSCs infiltration levels in GBM patients.We estimated the relationship between cell infiltration and prognosis of GBM.Subsequently, key risk genes were identified and prognostic models were constructed by LASSO-Cox analysis. The risk genes were validated by five independent external cohorts, single-cell RNA analysis, and immunohistochemistry of human GBM tissues. TIDE analysis predicted responsiveness to immune checkpoint inhibitors in different risk groups. Results: The MSCs infiltration level was negatively associated with survival in GBM patients. LOXL1, LOXL4, and GUCA1A are key risk genes that promote GBM progression and may act through complex intercellular communication.This research has provided a comprehensive study for exploring the MSCs infiltration environment on GBM progression, which could shed light on novel biomarkers and mechanisms involved in GBM progression.